Impacts of PROSPERA on Enrollment, School Trajectories, and Learning - Behrman, Jere R.; Parker, Susan W.; Todd, Petra (World Bank, Washington, DC, 2019)
Many studies have demonstrated that Mexico's conditional cash transfer program, PROSPERA, has substantial effects on educational attainment. Nevertheless, little evidence exists on whether increases in time spent in school have led to higher learning in the context of the poor areas where PROSPERA principally operates, which tend to have overall low school quality. This study combines data from nationwide achievement tests with administrative data on PROSPERA beneficiaries to estimate impacts on achievement tests. The analysis finds significant effects on learning, as measured by standardized achievement tests, on the order of magnitude of 0.05 to standard deviation, with larger effects for indigenous children. The analysis also confirms large effects on enrollment in secondary and high school, using administrative school enrollment data rather than self-reported household-level data, as generally used in previous studies. Finally, given the existence of several alternative tracks in secondary and high school, the study also examines where PROSPERA beneficiaries enroll. The findings show that most of the increase in enrollment occurs in tele-secondary schools and, at the high school level, in general high schools.